Nutritional Status, Fluid Intake, and Exercise Habits on the Incidence of Dehydration in Adolescents at SMP Negeri 1 Indralaya, Ogan Ilir Regency - Sinaga, Theresia Octaviani; Yuliarti; Desri Maulina Sari (JURNAL KESMAS DAN GIZI (JKG), 2025)
Dehydration is a condition that can reduce stamina, concentration, memory, and increase the risk of serious physical disorders. Adolescents are at higher risk of dehydration due to intense physical activity and fluid consumption patterns that are often insufficient. Fluid requirements in adolescents depend on various factors, including age, gender, level of physical activity, environmental conditions, and nutritional status. so special attention to hydration is needed. This study aims to analyze the relationship between nutritional status, fluid intake, and exercise habits with the incidence of dehydration in adolescents at SMP Negeri 1 Indralaya, Ogan Ilir Regency. This study used an analytical observational design with a cross-sectional approach. Data analysis used the chi-square statistical test with a 95% confidence level (? = 0.05). The sample consisted of 110 students. Data was collected through interviews, anthropometric measurements, and assessment of hydration levels using urine color check cards. The results of the study showed that 3.6% of adolescents were malnourished, 40.9 were overweight, 40.9% had an insufficient fluid intake, 80.9% exercised, and 79.1% were dehydrated. The results of statistical tests showed that there was no significant relationship between nutritional status (p=0.266), fluid intake (p=0.845), and exercise habits (p=0.816) with the hydration status of adolescents. Adolescents are advised to get used to routinely consuming water every day, especially before and after physical activity as an effort to prevent dehydration. In addition, it is necessary to avoid consuming sweet or caffeinated drinks that can increase the risk of dehydration. Schools can play an active role by providing easy access to drinking water, as well as providing education about the importance of good hydration for body health and supporting daily activities.